Palliative care for patients with glioma: A recent scientometric analysis of the Web of Science in 2022 - Xiao, Zhiyuan; Chen, Wenlin; Zhao, Haiyan; Wang, Hai; Zhao, Binghao; Liu, Delin; Yang, Tianrui; Liang, Tingyu; Xing, Hao; Wang, Yaning; Wang, Yuekun; Guo, Xiaopeng; et al. (Frontiers in Oncology, 2022)
Background: Patients with glioma present with complex palliative care needs throughout their disease trajectory. Scientometric analysis is effective and widely used to summarize the most influential studies within a certain field. We present the first scientometric analysis of palliative care for patients with glioma. Methods: We conducted a generalized search for articles on palliative care for glioma in the Web of Science database and evaluated the top 100 most frequently cited articles among 2542 articles. Results: The number of citations for the top 100 cited articles on palliative care for glioma ranged from 10 to 223. Most of these articles were published in oncology-specific journals (n=53) and palliative-specific journals (n=22). The USA, Australia and the Netherlands were top three countries contributing most of the articles (n=59). Most of the research methods were quantitative analyses, qualitative analyses and systematic reviews and meta-analyses (n=70). Articles were classified into 6 major categories based on research subjects and into 7 major categories based on research themes: quality of life (n=11); end-of-life symptoms and care (n=16); palliative and supportive care needs (n=35); advance care planning and decision making (n=4); psychological, social and spiritual needs (n=12); hospice utilization and referral (n=3); and others(n=19). Research subjects included patients (n=44), caregivers (n=16), patients and caregivers (n=20), literature (n=19), and health care providers (n=1). Conclusions: The results of the analysis indicated that patients diagnosed with glioma present a high palliative care needs, including physical, psychological, social, and spiritual needs. The caregiver’s burden and needs are important as well. The propotion of quantitative analyses, qualitative analyses, systematic reviews and meta-analyses is relatively high, but the number of randomized controlled trials (RCTs) was low. End of life care and supportive care needs appeared frequently. Thus, palliative care is an urgent need to be addressed in glioma management.